An enhanced matrix arithmetic package for IBM RISC 6000 - Bidon, Paul de Jesus
This study was conducted to enhance a Matrix Arithmetic (MA) program developed byDr. Salvador F. Reyes and make it adaptable to the IBM Risc 6000. The enhanced version is capable of handling larger matrices and finite element modelling which is one of its features. For the greatest possible portability, the program originally written in PASCAL has been rewritten in ANSI C.